High sensitivity c-reactive protein: uncovering the metabolic delinquent in young adults - Wan Omar, Wan Fatein Nabeila; Abdullah, Aszrin; A.Talib, Norlelawati; Ab Rahman, Jamalludin; Mohd Shah, Azarisman Shah (2020)
Background: Metabolic syndrome is a major risk factor for cardiovascular diseases. It is increasingly common among young adults. High- sensitivity C-reactive protein (HsCRP) has been recognised as a cardiovascular biomarker. This study evaluated the association between HsCRP and metabolic syndrome in Malaysian young adult population.